Low Environmental Temperature Exacerbates Severe Acute Respiratory Syndrome Coronavirus 2 Infection in Golden Syrian Hamsters. (18th September 2021) - Chan, Jasper Fuk Woo; Poon, Vincent Kwok Man; Chan, Chris Chung Sing; Chik, Kenn Ka Heng; Tsang, Jessica Oi Ling; Zou, Zijiao; Chan, Chris Chun Yiu; Lee, Andrew Chak Yiu; Li, Can; Liang, Ronghui; Cao, Jianli; Tang, Kaiming; et al.
Abstract: Background: The effect of low environmental temperature on viral shedding and disease severity of Coronavirus Disease 2019 (COVID-19) is uncertain. Methods: We investigated the virological, clinical, pathological, and immunological changes in hamsters housed at room (21°C), low (12–15°C), and high (30–33°C) temperature after challenge by 10 5 plaque-forming units of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Results: The nasal turbinate, trachea, and lung viral load and live virus titer were significantly higher (~0.5-log10 gene copies/β-actin, P  < .05) in the low-temperature group at 7 days postinfection (dpi). The low-temperature group also demonstrated significantly higher level of tumor necrosis factor-α, interferon-γ (IFN-γ), interleukin-1β, and C-C motif chemokine ligand 3, and lower level of the antiviral IFN-α in lung tissues at 4 dpi than the other 2 groups. Their lungs were grossly and diffusely hemorrhagic, with more severe and diffuse alveolar and peribronchiolar inflammatory infiltration, bronchial epithelial cell death, and significantly higher mean total lung histology scores. By 7 dpi, the low-temperature group still showed persistent and severe alveolar inflammation and hemorrhage, and little alveolar cell proliferative changes of recovery. The viral loads in the oral swabs of the low-temperature group were significantly higher than those of the other two groups from 10 to 17 dpi by about 0.5–1.0 log10 gene copies/β-actin. The mean neutralizing antibody titer of the low-temperature group was significantly ( P  < .05) lower than that of the room temperature group at 7 dpi and 30 dpi. Conclusions: This study provided in vivo evidence that low environmental temperature exacerbated the degree of virus shedding, disease severity, and tissue proinflammatory cytokines/chemokines expression, and suppressed the neutralizing antibody response of SARS-CoV-2-infected hamsters. Keeping warm in winter may reduce the severity of COVID-19. Abstract : SARS-CoV2-infected hamsters housed at low environmental temperature developed more severe disease than control hamsters housed at room temperature with higher respiratory tract viral burden and worsened clinical, immunological, and pathological features.